2018
DOI: 10.1177/1077558718754898
|View full text |Cite
|
Sign up to set email alerts
|

Effective Governance and Hospital Boards Revisited: Reflections on 25 Years of Research

Abstract: This study reviews and synthesizes empirical research literature focusing on the relationship between boards of directors and organizational effectiveness of U.S. hospitals. The study examines literature published in scholarly journals during the period of 1991-2017. Fifty-one empirical articles were identified that met the study's inclusion criteria. A framework from the corporate governance and nonprofit governance literature is used to classify the articles according to level of analysis (individual actors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 74 publications
(163 reference statements)
1
67
0
Order By: Relevance
“…Recent thinking suggests that rather than one or other of the theories being, in general, superior or preferred, context and desired outcomes should guide which theory (or combination) and related mechanisms best fit the circumstances. As Erwin et al suggest, 14 depending on the hospital or health system's mission or strategic goals, certain types of boards or board processes might be preferred and researchers should continue to study boards with this perspective in mind. For this study, we therefore draw on a realist-informed interpretation framework for healthcare boards as outlined in Table 1.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent thinking suggests that rather than one or other of the theories being, in general, superior or preferred, context and desired outcomes should guide which theory (or combination) and related mechanisms best fit the circumstances. As Erwin et al suggest, 14 depending on the hospital or health system's mission or strategic goals, certain types of boards or board processes might be preferred and researchers should continue to study boards with this perspective in mind. For this study, we therefore draw on a realist-informed interpretation framework for healthcare boards as outlined in Table 1.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…17 In an extensive US-focused review of hospital board governance research since 1990, Erwin et al found that the occupational background of board members influenced choice of focus, behavioural dynamics and the need for training to fulfil quality of care monitoring. 14 The work and functioning of boards is thus empirically variable not only as conditioned by composition and external forces but also by board processes and the deployment of the will and skill of individual board members, minimalist and maximalist board practices, and locked-in routines. [18][19][20][21] This line of research from the authors listed above emphasises board effort as discretionary, with board members having a choice to work more or less hard in the enactment of their role.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The necessary authority and support from the chancellors of the university and the MOHME for structural reforms had been established. While Lane et al (2018), in their study entitled "Study of the Relationship Between the Management of American Hospitals as a Board and Organizational Effectiveness", conducted a systematic review and concluded that due to the single structure of health care and the ever-changing and complex environment in which health care organizations (hospitals) operate, the use of corporate (hospital board) structure can lead to increased efficiency and performance of hospitals in the United States (34). Verzola et al (2017), in their study entitled "The Relationship Between Hospital Self-Governance and Performance in Public Hospitals in the UK" concluded that the increase in the delegation to governmental organizations did not find any significant functional difference in public hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Their services are normally offered freely to all citizens of the country (Young, 2016). Accordingly, they consume a substantial portion of the national resource envelope (Erwin et al , 2018). Due to scarcity of resources, they are faced with inadequate funding, as such; their per capita spending is low in spite a growing demand (Swanson et al , 2015; Asbu et al , 2012).…”
Section: Public Hospitals and Their Unique Challengesmentioning
confidence: 99%
“…In most developing countries, public hospitals are an integral component of the health system in the delivery of healthcare services to the majority of citizens (Abor, 2015; Eeckloo et al , 2004; SHOPS Project, 2012; Erwin et al , 2018). Although the public hospitals in most of these countries are units of the ministries of health or local governments, they are, however, established as standalone entities.…”
Section: Introductionmentioning
confidence: 99%